Association of Vitamin D Levels and Other Risk Factors with Asthma Exacerbations in Children - Syed ZaryabAhmed; Anila Jaleel; Kamran Hameed; Shehzad ShoukatNayani (ziauddin University, 2024)
Background: The risk factors for asthma exacerbations are well understood. However, the effect of vitamin D levels on number of asthma exacerbations per year is not clearly studied. The objective of the study was to ﬁnd out the association of serum vitamin D levels and asthma risk factors on asthma exacerbations. Methods: In this study, ninety-nine subjects from 5 to 15 years of age were recruited at an episode of acute exacerbation. It was a cross sectional study and carried out from 2012 to 2015. Pulmonary function test was done by spirometry. Asthma exacerbation was labeled when forced expiratory volume/ forced vital capacity (FEV1/FVC) ratio was less than 80% (American Thoracic Society). Global Initiative for Asthma (GINA) guidelines were used to classify asthma into mild, moderate and severe persistent asthma. Serum vitamin D levels were measured by chemiluminescence method. Pearson Chi-square test was applied and p value (p<0.05) was considered as statistically signiﬁcant. Results: Children who had exposure to animal dander had signiﬁcantly lower asthma exacerbations per year (p-value <0.046). There was no signiﬁcant association between vitamin D levels and number of exacerbations per years (p-value <0.099). Asthma was prevalent in girls of low socioeconomic status (SES) compared to males. However, there was no signiﬁcant association between smoke, exercise, home environment, food allergies, weather, pollen and dust with asthma exacerbations. Conclusion: Low levels of vitamin D were not associated with increased number of asthma exacerbations per year. However, children exposed to animal dander had lesser number of exacerbations per year (p-value <0.046). Keywords: Asthma; Vitamin D; Children; Exacerbations, Risk factors.